2021
DOI: 10.3390/ijerph18052705
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders among Italian Dentists and Dental Hygienists

Abstract: Dental professionals often perform physically and mentally demanding therapeutical procedures. They work maintaining muscular imbalance and asymmetrical positions for a long time. The aim of the study was to describe the prevalence and the factors associated to work-related musculoskeletal disorders (WMSD) among Italian dental professionals and the most affected body regions. A cross-sectional observational study was conducted between March 2019 and February 2020. The Nordic Musculoskeletal questionnaire (NMQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 31 publications
4
69
0
1
Order By: Relevance
“…The three phases of the study were carried out in October (the first year), February (the third year), and May (the fifth year). In the scientific literature, there is not a general agreement on the benefits of sporting activities in relation to MSDs among dentists nor dentistry students [ 12 , 14 , 22 , 23 , 24 , 25 , 27 , 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The three phases of the study were carried out in October (the first year), February (the third year), and May (the fifth year). In the scientific literature, there is not a general agreement on the benefits of sporting activities in relation to MSDs among dentists nor dentistry students [ 12 , 14 , 22 , 23 , 24 , 25 , 27 , 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is broad evidence of an association between work-related MSDs [ 2 ] and the dentistry profession [ 3 , 4 , 5 , 6 , 7 ]. The occurrence of MSDs among dentists varies between 47% and 93% in different studies [ 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Several studies among dentistry students showed the early onset of MSDs even during the undergraduate studies, where the occurrence ranged from 39% to 93% [ 8 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were found by Gandolfi et al among Italian dentists and dental hygienists. 32 The most affected body areas in their study population were also neck (59.9%) and shoulders (43.3%) followed by lumbar region (52.1%), dorsal region (37.7%) and wrists (30.6%).…”
Section: Discussionmentioning
confidence: 87%